Production performance and genetic similarities in Ukrainian and local brown quail - Firas Ibrahim; Arqam ALomari; Majid Sabri (Mesopotamia Journal of Agriculture)
Two lines of brown-colored Ukrainian (U) and local (L) quails, as well as cross (U×L) and reciprocal cross (L×U), were produced in the Agricultural Research Department's fields between March 1, 2023, and June 1, 2023. The purpose of the study was to determine the productive and genetic performance of these genetic groups. Over a period of eight weeks, the various birds' performances were evaluated using the: CEW g, HDP% and FCR (g feed/g egg mass). Moreover, estimates were also made of the genetic distance and similarity between the male and female of the groups. Therefore, the results were showed a significant increase (P < 0.05) in the Ukrainian quails and reciprocal cross (L×U) in the CEW (589.37 and 560.25) g and HDP (74.86 and 72.77) %, and a significant improvement (P < 0.05) in FCR (4.38 and 3.93) g feed/g egg mass) compared to the local quails and crossbreeding (U×L) quails. The genetic similarity between males and females of crossbreeding (U×L) is highest (0.8537), while that of local males and females of reciprocal cross (L ×U) is lowest (0.5244). while the genetic distance results supported the foregoing, with the local males and females of reciprocal crossbreeding (L ×U) having the highest genetic distance (0.6455) cM and the males and females of crossbreeding (U×L) having the least genetic distance (0.1582) cM.